An Analysis of Deixis Used by McDonald's Webpage Content - Alkana, Pansel (Universitas Sebelas Maret, 2022)
This research studies about deixis used by McDonald’s webpage content. There are two objectives of this research. The first objective is to identify the types of deixis used by McDonald’s webpage content and the second objective is to analyze the referents meaning of the deixis used by McDonald’s webpage content. The research method is descriptive qualitative method with data analysis technique, that is content analysis design. The result of the research shows that there were 94 deixis used by McDonald’s web page content. The data of deixis types are classified into five types. They are person deixis, time deixis, place deixis, social deixis and discourse deixis. In this research, person deixis became the most dominant type of deixis used by McDonald’s. person deixis in addressing McDonald’s teams and McDonald’s customers. The usage of social deixis to address McDonald’s partners and the relation, discourse deixis for explaining the discourse in upcoming and prior portion about the McDonald’s content in the McDonald’s webpage. Next, place deixis is used to mention the location and the time deixis is used for referring the specific time.